Visual Literacy Instruction at Scale: Developing Asynchronous Learning Objects for First-Year Art and Design Students - Jacqueline Huddle; Sarah Carter (Communications in Information Literacy)
While learning modules are not new to academic librarianship, student-centered, asynchronous learning modules are an innovative approach not commonly considered within the academic librarianship literature. This article discusses the development and implementation of visual literacy asynchronous learning modules created by two librarians for a cohort of first-year studio art students. In creating these modules, the goal was to offer studio art students visual literacy instruction specific to their personal interests and future careers. Specifically, this article discusses the module design process and how student-centered learning can be incorporated into modules in order to offer deep learning opportunities.